2016
DOI: 10.1126/scitranslmed.aad3270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Olyset Duo net against insecticide-resistant mosquito vectors of malaria

Abstract: Olyset Duo is a new long-lasting insecticidal net treated with permethrin (a pyrethroid) and pyriproxyfen, an insect growth regulator that disrupts the maturation of oocytes in mosquitoes exposed to the net. We tested the Olyset Duo net against pyrethroid-resistant Anopheles gambiae mosquitoes, which transmit malaria parasites, in laboratory bioassays and in a trial in Benin using experimental huts that closely resemble local habitations. Host-seeking mosquitoes that entered to feed were free to contact the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 19 publications
4
40
3
Order By: Relevance
“…Quite often, LLINs and insecticide sprays were used in conjunction, as it is believed that relying on both products simultaneously is more effective than a single tool. Several studies reported the significant effect to combine both LLINs and IRS usage on malaria, particularly in areas where pyrethroid resistance is high [2,24]. However, the rate of multiple tools observed in our study was still low, perhaps, because the spray is too expensive.…”
Section: Discussioncontrasting
confidence: 52%
“…Quite often, LLINs and insecticide sprays were used in conjunction, as it is believed that relying on both products simultaneously is more effective than a single tool. Several studies reported the significant effect to combine both LLINs and IRS usage on malaria, particularly in areas where pyrethroid resistance is high [2,24]. However, the rate of multiple tools observed in our study was still low, perhaps, because the spray is too expensive.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, several studies show continued impact of Olyset nets in experimental hut studies in spite of strong resistance characterized using standard laboratory exposures (Churcher et al., ; Strode et al., ). For example, a recent experimental hut study conducted in an area of >100‐fold permethrin resistance in Benin showed an Olyset LLIN to cause an average of 32% mortality, compared with 5% mortality using an untreated control net (Ngufor et al., ). Further, relative to huts with an untreated net, the LLIN increased the proportion of mosquitoes exiting the huts by 19% and reduced blood feeding by 66% (Ngufor et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent experimental hut study conducted in an area of >100‐fold permethrin resistance in Benin showed an Olyset LLIN to cause an average of 32% mortality, compared with 5% mortality using an untreated control net (Ngufor et al., ). Further, relative to huts with an untreated net, the LLIN increased the proportion of mosquitoes exiting the huts by 19% and reduced blood feeding by 66% (Ngufor et al., ). These results are broadly consistent with our experimental hut studies conducted using PermaNet 2.0.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that the present comparative study of polypropylene, polyester and polyethylene LNs would provide evidence to help calculate that criterion for different types of LN. Looking forward beyond current pyrethroid LNs to a future of nets treated with alternative insecticides to combat pyrethroid resistant mosquitoes, more durable fabrics may be necessary to maintain LN unit costs to a reasonable level [44, 45]. …”
Section: Discussionmentioning
confidence: 99%